Effects of vibration combined with unstable surface training on somersault athletic performance of artistic gymnasts - Chen, I.-H.; Kao, Y.-H.; Weng, S.-H.; Huang, C.-F. (ISBS Proceedings Archive (Michigan), 2023)
Purpose: The effect of 4 and 8 weeks of combined training on the somersault performance of artistic gymnasts. Methods: 16 male college gymnasts were randomly paired and divided into combined (CT) and vibration (VT) groups for eight weeks of training. One force plate was used to collect the front and back somersault data before, after four, and eight weeks of training. The significance level was set at a = .05. Results: Back somersault, the take-off force and somersault height of CT were better than pre-test, and the somersault height was better than VT. Front somersault, the take-off force, impulse, and somersault height of CT are better than pre-test, and the somersault height and take-off force are better than VT. Conclusion: The four and eight weeks of vibration combined with unstable surface training can improve the performance of front and back somersaults.